1994
DOI: 10.1152/ajpheart.1994.266.3.h1069
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular autoregulation during fetal development in sheep

Abstract: There are scant data regarding the development of cerebrovascular autoregulation in fetuses. We tested the hypothesis that a decrease in cerebrovascular resistance (CVR) at reduced cerebral perfusion pressure (CPP) is absent in midgestation and near-term fetal sheep. Catheters were chronically implanted for microsphere determination of cerebral blood flow (CBF) in 9 fetuses at 92 days and in 10 fetuses at 132 days gestation (full term = 145 days). CPP was reduced by ventricular infusion of artificial cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…Furthermore, the cerebral vasoconstrictive effect was blocked by phenoxybenzamine, which also blocked the increase in MAP, thus effectively eliminating the "need" for an autoregulatory response. Studies in sheep have demonstrated that cerebral autoregulation is intact in preterm and near-term fetuses (13,22), although the autoregulatory range is narrow and the lower limit is near the resting blood pressure. Thus it is not known whether this autoregulatory response could occur in hypotensive or sick animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the cerebral vasoconstrictive effect was blocked by phenoxybenzamine, which also blocked the increase in MAP, thus effectively eliminating the "need" for an autoregulatory response. Studies in sheep have demonstrated that cerebral autoregulation is intact in preterm and near-term fetuses (13,22), although the autoregulatory range is narrow and the lower limit is near the resting blood pressure. Thus it is not known whether this autoregulatory response could occur in hypotensive or sick animals.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the fetal sheep model is that physiological studies can be performed at a critical stage of brain development, i.e., 90 days of gestation, in which there is brain growth and onset of organized electrocortical activity preceding a period of intense neuroglial multiplication and myelination (17). Finally, previous cerebrovascular studies in immature fetal sheep demonstrate that they have lower CBF and CMRO 2 as well as limited autoregulation and blunted responses to hypoxemia compared with near-term fetuses (9,10,13). A limitation of this model is the potential difficulty in extrapolating results obtained in fetuses to newborns, particularly the influence of the uteroplacental circulation and fetal physiology on the cerebrovascular and systemic responses we observed.…”
Section: Discussionmentioning
confidence: 99%
“…The sheep fetus displays cerebral hemodynamics similar to humans and permits repeated physiological measurements in utero in the unanesthetized state. Importantly, similar to the human fetus [77][78][79][80], the fetal sheep displays a very limited range of cerebral autoregulation under normal conditions and a pressure-passive cerebral circulation when subjected to systemic hypoxia and associated hypotension [66,[81][82][83][84]. Moreover, measurements of BP, electroencephalography, blood oxygenation, and other vital variables can be correlated with acute changes in cerebral blood flow and metabolism.…”
Section: Hypoxia-ischemia In Fetal Sheep Generates Pathological Featumentioning
confidence: 99%
“…The importance of the central autonomic system and adrenal stress hormones remains unclear, as well as the systemic blood concentrations of metabolic substrates, such as glucose and products such as lactate. The fetal sheep brain, in particular when immature and hypoxemic, has essentially no ability to autoregulate [81][82][83]. Hence, in umbilical cord occlusion models, the fall in BP exacerbates the fetal brain hypoxia with a consequent reduction in CBF that leads to partial ischemia.…”
Section: Pathophysiological Mechanisms Of Wmi Related To the Brachiocmentioning
confidence: 99%
“…The mammalian cerebral vasculature develops muscularity at approximately two-thirds gestation, which corresponds to 26-27 weeks' gestation in humans, so extremely premature infants may lack the necessary arteriolar tone needed to impart pressure autoregulation. 23,24 The ontogeny of autoregulation is therefore germane to our interpretation of pressurepassivity in premature infants.…”
Section: Introductionmentioning
confidence: 99%